A New Pattern to Improving Student Physics Learning Outcomes - Zakirman; Widiasih Widiasih; Dodi Sukmayadi; Rika Aprianti; Khoirotun Nadiyyah (Postgraduate, University of Mataram, 2023)
The low student learning outcomes in Physics can be observed by the decreasing average student learning outcomes in the last 3 years at SMA 1 Suger. Lack of precise strategy selection is a major factor in influencing student learning outcomes in Physics. In addition to learning strategy factors, students' initial abilities can be considered by teachers in choosing learning strategies to improve student learning outcomes. The purpose of this study was to compare students' learning outcomes in physics between classes using guided inquiry and discovery strategies by considering initial ability as a moderator variable. This type of research is a quasi-experimental, the sampling technique used is random sampling. This research was conducted at SMA 1 Suger, Padang Pariaman Regency. The results of the study show 1) there is a significant difference between the learning outcomes of physics students who learn to use guided inquiry and discovery strategies, 2) there are significant differences in learning outcomes between students with high and low initial abilities, 3) there is no interaction between the use of strategies and abilities early in influencing student learning outcomes.